Effect of Compression Tights on Performance During Intense Pedalling Exercise (Journal of Fiber Bioengineering and Informatics, 2014)
The purpose of this study was to investigate the effect of wearing tights on performance while pedallingat high intensity. Eight male undergraduates majored in sports science volunteered to participate in theexperiments. Subjects wearing Gradient Compression Tights (GCT) or loose pants as control condition(CONT), pedalled on the power bicycle-ergometer at 180W/60RPM till exhaustion. Surface EMG wasrecorded at the surface of Rectus Femoris (RF), Vastus Lateralis (VL), Biceps Femoris (BF) belly,Tibialis Anterior (TA) belly and Medial Gastrocnemius (GM) and the heart rate was also monitored. Itwas confirmed that the GCT exerted gradient pressure distribution on the surface of lower limbs. Suchgradient pressure helped to increase the venous return and the heart output, resulted in relatively lowerheart rate and longer pedalling duration. The EMG analysis showed significant effect on the averageEMG (aEMG) and the Mean Power Frequency (MPF) caused by GCT. Based on a pattern of motorrecruitment with the recurrent inhibition, it was speculated that the pressure might enhance the activityof inhibition interneurones, more Motor Units (MU) of low thresholds were inhibited. Due to the lesscontribution of low-frequency components, the aEMG was lower and the MPF was higher.